Respuesta :

Answer:

AB/AD = AD/AC

Step-by-step explanation:

From the triangle given, we can get the required expression to calculate CD using the altitude theorem as shown:

AB/CB = CB/DB (Hypotenuse/Adjacent side using the similar triangle ABC and CDB)

AB/AC = AC/AD (Hypotenuse/Opposite side using the similar triangle ABC and ACD)

BD/CD = CD/AD (Adjacent/Opposite side using the similar triangle BCD and ACD)

Hence the odd one out will be option C AB/AD = AD/AC (since there is no altitude CD in the expression)

Answer:

AB/AD = AD/AC

Step-by-step explanation:

Had it on my quiz